2017
DOI: 10.1177/2047487316682348
|View full text |Cite
|
Sign up to set email alerts
|

The perioperative dental screening and management of patients undergoing cardiothoracic, vascular surgery and other cardiovascular invasive procedures: A systematic review

Abstract: Background One controversial issue in the relationship between oral care and cardiovascular diseases is how and whether to manage oral infections prior to cardiovascular surgery or other cardiovascular invasive procedures. Design We designed a systematic review to assess the information available on three main questions. Is there an agreement on the need for dental evaluation and treatment before cardiovascular interventions? Are consistent clinical recommendations or protocols available? Is dental treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
(193 reference statements)
4
30
0
4
Order By: Relevance
“…25 A systematic review suggested that there is a general consensus for preventive screening and treatment for dental infections in the patients undergoing cardiothoracic and cardiovascular intervention. 28 Previously, one study has proposed that periodontitis is an independent factor of arrhythmic events in patients with AF and AF highly occurs in patients with severe periodontitis. 29 Considering HF, performing tooth scaling is associated with decreased risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…25 A systematic review suggested that there is a general consensus for preventive screening and treatment for dental infections in the patients undergoing cardiothoracic and cardiovascular intervention. 28 Previously, one study has proposed that periodontitis is an independent factor of arrhythmic events in patients with AF and AF highly occurs in patients with severe periodontitis. 29 Considering HF, performing tooth scaling is associated with decreased risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one study reported a higher incidence of IE in treated patients compared to patients who did not receive dental treatment prior to heart valve surgery 29 . Meta‐analysis studies have shown that there are no differences in all‐cause mortality in patients who did and did not receive dental treatment before surgery 30,31 . Dental infection should not be neglected prior to heart surgery, and the extent of dental treatment should be tailored to the patient's clinical status and performed by a dental/medical team.…”
Section: Dental Treatment Before Heart Valve Surgerymentioning
confidence: 99%
“…In recent studies, the multidisciplinary approach has attracted attention for reducing the rate of postoperative complications after gastrointestinal surgery, including via patient nutrition management, chemical bowel preparation and early-phase rehabilitation [1][2][3] . To this end, some studies have shown the effectiveness of managing the oral function in order to prevent aspiration pneumonia [4][5][6] , infectious endocarditis [7][8][9] or postoperative complications in head and neck surgery 10) and esophageal surgery 6) . It is easy to understand how these efforts can help reduce aspiration pneumonia or wound infection in cases of head, neck or esophageal surgery; however, the influence of oral management on postoperative infectious complications (POICs) following surgery of the more distal gastrointestinal tract, such as stomach or colorectal surgery, remains unclear.…”
Section: Introductionmentioning
confidence: 99%